Verbal Aggression: Linguistic and Legal Aspect - N. I. Yelnikova; O. H. Yushkevych (Law and Safety)
The article examines the phenomenon of verbal aggression as a linguistic and legal problem which, under certain conditions, can be qualified as an administrative or criminal offence. The verbal aggression is defined as a conscious communicative strategy aimed at achieving certain goals through the use of language. Theoretical aspects of communication strategies are characterised. The key characteristics, forms of manifestation and consequences of verbal aggression in the context of interpersonal communication are analysed. Various forms of verbal aggression are considered, including insults, threats, criticism, irony, manipulation and ignoring. Particular attention is paid to the analysis of linguistic means used to implement verbal aggression as a communication strategy. The lexical, syntactic and stylistic features of aggressive statements, as well as their impact on the emotional state of the interlocutor are identified.